Drug resistant fungal infections An emerging threat (Journal of Dhaka National Medical College & Hospital, 2018)
Drug resistance has become an important problem leading to significant negative social, psychological, and occupational health effects and quality of life. Clinical failure and relapses have been observed in patients treated with antifungal drugs. Now a days, Antifungal drug resistance is becoming an emerging threat in management of fungal infections especially in immunocompromised patients. Early recognition and treatment is essential to reduce morbidity and possibility of transmission. The increased use, inappropriate prescribing and over the counter sale of antifungal agents has also added in the development of resistance to these drugs. The level of resistance to antifungal agents is still relatively low, but there is a possibility of antifungal resistance becoming a crucial determinant of outcome following antifungal therapy in future. In addition to discussing the molecular mechanisms of antifungal resistance, this article elaborates on the current concept of clinical resistance, which is critical to the understanding of treatment failure in patients with fungal infections.J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 52-56